The Effect of Skul.id-Based Blended Learning with the Station Rotation Model on Students’ Perceptions, Activities, and Science Learning Outcomes at the Junior High School - Andi Hasnah; Firdaus Daud; Oslan Jumadi; Yusminah Hala; Faisal Faisal (Postgraduate, University of Mataram, 2026)
The Skul.id platform is a local Learning Management System (LMS) designed to support blended learning through features such as access to learning materials, assignment submission, and online evaluation. This study aimed to examine the effectiveness of Skul.id-based blended learning with the station rotation model on students’ perceptions, learning activities, and science learning outcomes. A quasi-experimental method with a nonequivalent control group design was employed, involving 54 eighth-grade students. The experimental group received blended learning with station rotation, while the control group received blended learning without station rotation. Data were collected using questionnaires, observation sheets, and learning achievement tests. The results showed significant differences between the two groups. The experimental group demonstrated very positive perceptions (96.30%), very high learning activity (100%), and higher learning outcomes with a mean posttest score of 77.78 and an N-gain of 0.56. In contrast, the control group showed positive perceptions (77.78%), active learning activity (92.59%), and lower learning outcomes with a mean posttest score of 65.48 and an N-gain of 0.36. Although both N-gain values were categorized as moderate, the experimental group achieved a substantially higher improvement. Independent sample t-test results confirmed statistically significant differences in perceptions, learning activities, and learning outcomes (p < 0.05). These findings indicate that Skul.id-based blended learning with station rotation is more effective in improving students’ perceptions, learning activities, and science learning outcomes